2017
DOI: 10.1016/j.eats.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Combined Anterior and Anterolateral Stabilization of the Knee Using Hamstring Tendons and Adjustable-Loop Suspensory Fixation Device: Surgical Technique

Abstract: Despite the numerous techniques described regarding isolated anterior cruciate ligament (ACL) reconstruction, many authors have reported that residual knee rotational instability is not always eliminated. The combination of lateral extra-articular knee tenodesis and ACL reconstruction is an alternative surgical approach with very promising clinical results. The purpose of this article is to describe a reliable and reproducible technique of combined ACL reconstruction and lateral extra-articular knee tenodesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Different fixation methods have been reported in the literature when ACLR and ALLR are considered. 19 Sonnery-Cottet et al 19 fixed their autologous hamstring tendon with aperture screws, and Boutsiadis et al 20 used adjustableloop suspensory fixation device with aperture screws. Both groups recreated SB ACLR and ALLR successfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different fixation methods have been reported in the literature when ACLR and ALLR are considered. 19 Sonnery-Cottet et al 19 fixed their autologous hamstring tendon with aperture screws, and Boutsiadis et al 20 used adjustableloop suspensory fixation device with aperture screws. Both groups recreated SB ACLR and ALLR successfully.…”
Section: Discussionmentioning
confidence: 99%
“… 19 fixed their autologous hamstring tendon with aperture screws, and Boutsiadis et al. 20 used adjustable-loop suspensory fixation device with aperture screws. Both groups recreated SB ACLR and ALLR successfully.…”
Section: Discussionmentioning
confidence: 99%
“…This ACLR+LET technique was previously described by Boutsiadis et al 2 It entailed the same skin incision and approach as for the ST4 group. The gracilis and semitendinosus tendons were harvested and completely detached from their tibial attachment.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, LET has been used in addition to ACLR to add restriction to internal tibial rotation forces, 4 and different authors have shown their techniques to achieve this task. 5 , 6 , 7 , 8 , 9 Also, biomechanical studies have compared different techniques for LET procedures. 10 …”
mentioning
confidence: 99%
“…4 Recently, LET has been used in addition to ACLR to add restriction to internal tibial rotation forces, 4 and different authors have shown their techniques to achieve this task. [5][6][7][8][9] Also, biomechanical studies have compared different techniques for LET procedures. 10 This article aims to describe our technique performing a modified Macintosh LET as an addition to ACLR in selected patients who require extra internal tibial rotation control.…”
mentioning
confidence: 99%